2020
DOI: 10.37796/2211-8039.1015
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of monocyte subsets is linked to the severity of atherosclerosis in patients with ischemic heart disease: a case-control study

Abstract: Background: Monocytes are recognized as central cells in the progression of atherosclerosis, and are subcategorized into classical (CD14++CD16 lo), intermediate (CD14++CD16 hi) and non-classical (CD14+CD16 hi) subsets. Purpose: The present study aimed to assess the relationships between different subsets of monocytes, metabolic and inflammatory factors in patients with stable coronary heart disease. Methods: A total of 26 patients (both men and women) with stable ischemic heart disease (IHD) were recruited. Am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Mainly they represent a patrolling monocyte population, being found close to the vessel wall in the circulation and scavenging oxidized lipids, cellular debris and pathogens ( 58 ). According to our data the frequency of non-classical monocytes inversely correlates with the severity of atherosclerosis in patients with stable coronary artery disease ( 63 ). One may speculate that it is non-classical monocytes that are essential for the resolution of inflammation in AMI, as late recruitment of monocytes in the models of acute inflammation did not depend on the CCR2 expression ( 64 ).…”
Section: Monocytes/macrophagesmentioning
confidence: 71%
“…Mainly they represent a patrolling monocyte population, being found close to the vessel wall in the circulation and scavenging oxidized lipids, cellular debris and pathogens ( 58 ). According to our data the frequency of non-classical monocytes inversely correlates with the severity of atherosclerosis in patients with stable coronary artery disease ( 63 ). One may speculate that it is non-classical monocytes that are essential for the resolution of inflammation in AMI, as late recruitment of monocytes in the models of acute inflammation did not depend on the CCR2 expression ( 64 ).…”
Section: Monocytes/macrophagesmentioning
confidence: 71%
“…It was reported that HDL blocks monocyte activation, proliferation and differentiation, which reduces the inflammatory response that monocytes induce 43 . Kologrivova et al 47 . observed a direct correlation between TG/HDL and circulating CD16 + monocytes.…”
Section: Discussionmentioning
confidence: 98%
“…The frequency of monocyte subsets has been linked to severity of atherosclerosis in patients with stable coronary heart disease (44). We measured two subsets of circulating monocytes, defined by surface expression levels of CD163 and CD14.…”
Section: Igf-1 Decreases Cell Apoptosis Reduces Systemic Oxidative St...mentioning
confidence: 99%